Strategi Guru dalam Menghadapi Keterbatasan Sumber Daya Pendidikan di SMA Negeri 3 Amarasi Selatan - Darius Kristofel Amtiran (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
This study aims to analyze teachers’ strategies in addressing limited educational resources at SMA Negeri 3 Amarasi Selatan, Kupang Regency, and their impact on learning quality. This research uses a qualitative case study approach. Data were obtained through observations, in-depth interviews, and documentation involving the principal and four subject teachers. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that teachers employ several adaptive strategies such as contextual learning innovations, utilization of local resources, collaboration with parents and the community, and independent professional development. These strategies help sustain the teaching-learning process despite limited facilities. However, constraints such as inadequate laboratories, limited textbooks, poor classroom conditions, and restricted internet access still negatively affect learning quality, increase dropout risks, lower teacher motivation, and hinder educational innovation. This study highlights the strategic role of teachers as agents of change and stresses the urgency of government support to ensure equitable distribution of educational resources in remote areas.